Physiological parameters and acid-base status in horses competing in an 80 km endurance race at 2600 m above sea level - Valderrama Martínez, Claudia (2020)
The aim of this study was to determine some physiological parameters and characterize the changes of the acid-base state in enduro horses that competed in an 80 km race at an altitude of 2600 m above sea level. Blood samples were taken from 11 horses before the start (T0), at the end (T1) and one hour after the end of the race (T2). Blood values of variables determining the acid-base state, muscle enzymes, electrolytes, metabolites, hematocrit and plasma proteins were determined. Acid-base disorders were determined using the Henderson-Hasselbach and Stewart approximations and the change in plasma volume was calculated. Differences were found in the variables of CO2 pressure, non-volatile buffer anions, HCO3-, plasma proteins, muscle enzymes, metabolites, sodium, chloride, potassium, ionized calcium and phosphates. Hyperlactatemic acidosis, respiratory alkalosis, strong ion alkalosis and non-volatile buffer anion acidosis were the acid-base disorders presented. The results were not different from those reported in studies conducted at less than 1000 meters above sea level., which allows to conclude that an altitude of 2600 m may not affect athletic performance in enduro horses.